Contrasting presentation of solitary scapular osteochondroma: a report of three cases and review of literature - Varughese, Ajay Alex; Pandey, Ritesh Arvind; Paul, Rajesh; John, Bobby (International Journal of Research in Orthopaedics, 2020)
Scapular osteochondroma can have unusual manifestations like pseudo-winging and snapping syndrome in ventrally located lesions. Dorsally located lesions cause a cosmetic blemish and difficulty in lying supine. We present a series of 3 cases of scapular osteochondroma with varying presentations. One was a ventral surface (subscapular) osteochondroma which presented with pseudo winging and snapping syndrome and 2 were dorsal surface osteochondromas which presented with prominence at the back and difficulty in lying supine. All were treated surgically with good functional and cosmetic results. Surgical resection of tumor is the treatment of choice. An appropriate surgical approach should be chosen depending on the location of tumor. We propose the use of trapezius sparing approach and splitting the scapular apophysis for subscapular osteochondroma in children as it produces less soft tissue damage, is easy to repair and allows early rehabilitation.